CRITICAL POINT INDICATOR OF FATAL ACCIDENTS: A CONTRIBUTION TO THE REDUCTION OF TRAFFIC DEATHS - Moura, Djairlon Henrique (Seven Editora, 2025)
Despite significant advances in road safety research, gaps remain in measuring and monitoring the factors that determine severe traffic crashes. This study proposes the Critical Point Indicator for Fatal Traffic Crashes (CPIF), a tool designed to identify and prioritize highway segments with the highest concentration of fatalities. More than 2.1 million crash records were analyzed from 2007 to 2024, involving 4.7 million people and resulting in 121,661 deaths on Brazilian federal highways. The research also compared trends across three groups of countries — the nine largest by area, nine South American nations, and 22 European countries — revealing an increase in fatalities since 2019 and conceptual divergences regarding the definition of “critical point” among national and international institutions. The results highlight distinct spatial and causal patterns that demand targeted engineering and policy responses. The CPIF is presented as a decision-support instrument to optimize public investments, guide localized interventions, and contribute to achieving the UN and Brazil’s PNATRANS goal of reducing road deaths by 50% by 2030. DOI: https://doi.org/10.56238/sevened2025.036-040